2011
DOI: 10.1007/s00418-011-0816-0
|View full text |Cite
|
Sign up to set email alerts
|

Segregation during cleavage in the mammalian embryo? A critical comparison of whole-mount/CLSM and section immunohistochemistry casts doubts on segregation of axis-relevant leptin domains in the rabbit

Abstract: Segregation of certain cytoplasmic molecules during cleavage and blastocyst formation that was previously reported to occur in the human and the mouse (Antczak and Van Blerkom Mol Hum Reprod 3:1067-1086, 1997; Antczak and Van Blerkom Hum Reprod 14:429-447, 1999) has been reinvestigated in the rabbit model. Additional methodology was used and two approaches were compared: (1) whole-mount immunohistochemistry followed by confocal laser scanning microscopy (WM-IHC/CLSM) versus (2) IHC performed on histological se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…, 2003) and is the most differently expressed among the EPI-related mRNAs that are detected at the 2-cell stage, directly followed by Pou5f1 ( Oct4 ). As we queried the expression of Cops3 in situ using Stellaris® probes in confocal imaging, we knew we had to be very cautious, because: (i) non-homogeneous signal distribution may be caused by the fixative (Littwin and Denker, 2011); (ii) extended focus in a spherical object is bound to create projection images with a gradient of fluorescence between the centre and periphery and (iii) differences in fluorescence intensity in the Z dimension can be due to bleaching. Therefore, we examined the sister blastomeres next to each other in the sole equatorial region (10 confocal slices corresponding to a total of 2.22 μm) to minimize these problems.…”
Section: Discussionmentioning
confidence: 99%
“…, 2003) and is the most differently expressed among the EPI-related mRNAs that are detected at the 2-cell stage, directly followed by Pou5f1 ( Oct4 ). As we queried the expression of Cops3 in situ using Stellaris® probes in confocal imaging, we knew we had to be very cautious, because: (i) non-homogeneous signal distribution may be caused by the fixative (Littwin and Denker, 2011); (ii) extended focus in a spherical object is bound to create projection images with a gradient of fluorescence between the centre and periphery and (iii) differences in fluorescence intensity in the Z dimension can be due to bleaching. Therefore, we examined the sister blastomeres next to each other in the sole equatorial region (10 confocal slices corresponding to a total of 2.22 μm) to minimize these problems.…”
Section: Discussionmentioning
confidence: 99%
“…Sadly, abovementioned findings have emerged to be not reproducible, possibly due to the methodology used [immunohistochemistry, IHC, performed on whole-mount (WM) in conjunction with confocal laser scanning microscopy, WMIHC/CLSM]. This prompted Littwin and Denker (2011) to resume work on this open issue using a rabbit model. The authors performed, as previously, WMIHC/ CLSM, but this time compared acquired results with section immunohistochemistry (S-ICH).…”
Section: Developmentmentioning
confidence: 82%
“…In embryos of mouse, human, bovine, chicken, and rabbit species, leptin is present and has specific spatial localization [121,122,128,[156][157][158] (Table 5). In these studies, authors demonstrated that after fertilization, leptin becomes differentially distributed among the inner and outer blastomeres of the morula stage embryo in a pattern that persists with respect to the ICM and trophoblast through the hatched blastocyst stage, suggesting an important role of leptin in early embryo development.…”
Section: Fertilization and Embryo Developmentmentioning
confidence: 99%